2012
DOI: 10.1074/jbc.m111.332528
|View full text |Cite
|
Sign up to set email alerts
|

GABRB3 Mutation, G32R, Associated with Childhood Absence Epilepsy Alters α1β3γ2L γ-Aminobutyric Acid Type A (GABAA) Receptor Expression and Channel Gating

Abstract: Background: A GABRB3 mutation has been associated with childhood absence epilepsy and ␤3 subunit hyperglycosylation. Results: The mutation altered subunit expression and reduced GABA A receptor function independent of N-glycosylation. Conclusion: The mutation introduced a charged residue predicted to alter subunit interactions. Significance: The distal N terminus of GABA A receptor subunits may play an unexpected role in receptor assembly and channel gating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 48 publications
0
49
0
Order By: Relevance
“…Due to the inefficient assembly of mutant γ2 subunit-containing pentameric receptors, receptors with a different stoichiometry (α1β2 dimeric receptors) were able to be assembled. We previously reported two other mutations within structural loops contributing to interface interactions with similar fates: the β3 subunit mutation G32R located at the γ+/β− subunit interface (Gurba et al, 2012), and the γ2 subunit mutation R177G located at the α+/γ− interface (Audenaert et al, 2006). Both GABRB3(G32R) and GABRG2(R177G) mutations were shown to decrease surface levels of mutant γ2L subunits and increase surface levels of αβ heteropentamers and/or β3 homopentamers, indicating a common molecular mechanism shared by this group of mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the inefficient assembly of mutant γ2 subunit-containing pentameric receptors, receptors with a different stoichiometry (α1β2 dimeric receptors) were able to be assembled. We previously reported two other mutations within structural loops contributing to interface interactions with similar fates: the β3 subunit mutation G32R located at the γ+/β− subunit interface (Gurba et al, 2012), and the γ2 subunit mutation R177G located at the α+/γ− interface (Audenaert et al, 2006). Both GABRB3(G32R) and GABRG2(R177G) mutations were shown to decrease surface levels of mutant γ2L subunits and increase surface levels of αβ heteropentamers and/or β3 homopentamers, indicating a common molecular mechanism shared by this group of mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that altered N-glycosylation of some GABA A R subunits in model systems affects the processing, assembly, receptor stability, and cell surface expression of mature GABA A Rs, as well as affecting channel gating properties and receptor function (Buller et al, 1994;Gurba et al, 2012;Lo et al, 2010;Tanaka et al, 2008). N-glycosylation has a functional role regulating forward trafficking of proteins along the secretory pathway from the ER through the Golgi before vesicular transport to the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations of consensus sequences on the b2 subunit inhibiting N-glycosylation have been shown to decrease peak current amplitude and mean channel open time of GABA A Rs and, in an N-glycosylation consensus sequence-specific manner, have variable effects on subunit stability, assembly of receptors in the ER, and expression of N-glycosylation-deficient b2 subunit-containing receptors in the plasma membrane (Lo et al, 2010). It has been postulated that aberrant glycosylation of specific GABA A R subunits may lead to altered protein folding and tertiary structure, causing the assembly of correctly N-glycosylated subunits to be more energetically favorable and altering GABA A R subunit stoichiometry in the plasma membrane (Gurba et al, 2012). Alternatively, it has been suggested that incorrect N-glycosylation may impair receptor trafficking to the plasma membrane, reducing GABA-evoked currents and decreasing the efficacy of GABAergic signaling (Tanaka et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Although ab-heteromers lacking the g subunit are functional and exhibit higher potency (e.g., lower EC 50 ) for GABA than abg assemblies, the loss of the g subunit impairs the targeting of ab receptors to the synapse via the loss of interactions with the GABARAP-gephyrin trafficking-scaffolding machinery. In addition, b3(P11S), b3(S15F), and b3(G32R) all result in N-linked glycosylation errors, impairing normal GABA receptor-mediated inhibition, resulting in GEFS1 and/or DS (Tanaka et al, 2008;Gurba et al, 2012). In addition to those noted above, 10 more mutations in the most abundant a subunit, a1, have been linked with idiopathic epilepsies, Dravet syndrome, and epileptic encephalopathies.…”
Section: Gaba a Receptorsmentioning
confidence: 95%
“…However, as with the majority of GABR SNPs, more data are needed to specifically understand how each SNP leads to a change in GABAergic function. If the same approach taken in the evaluation of epilepsy-linked mutations can be applied here (e.g., Gallagher et al, 2007;Gurba et al, 2012), our understanding of addiction could be substantially enhanced.…”
Section: Gaba a Receptorsmentioning
confidence: 99%